2018
DOI: 10.3390/ijms19113330
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Cryopreservation System: An Effective Method for Cell Storage

Abstract: At present, living cells are widely used in cell transplantation and tissue engineering. Many efforts have been made aiming towards the use of a large number of living cells with high activity and integrated functionality. Currently, cryopreservation has become well-established and is effective for the long-term storage of cells. However, it is still a major challenge to inhibit cell damage, such as from solution injury, ice injury, recrystallization and osmotic injury during the thawing process, and the cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…Due to their distinguished properties, such as ease of gelling with divalent metal cations (ionic cross-linking) thus forming an “egg-box” structure [ 5 ] and 3D environment close to the extracellular matrix of native tissues, high biocompatibility, low immunogenicity in vivo and controlled biodegradability [ 6 , 7 , 8 ], alginate hydrogels have been widely used in medicine and medicine-related research [ 3 ]. This includes delivery vehicles in cancer treatment [ 9 ], wound dressing [ 4 ], mammalian cell culture in biomedical studies, tissue regeneration with protein and cell delivery, engineering of various tissues/organs [ 10 , 11 , 12 ] including bladder regeneration [ 13 ], bone tissue engineering [ 14 ], and a protective carrier for cryopreservation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their distinguished properties, such as ease of gelling with divalent metal cations (ionic cross-linking) thus forming an “egg-box” structure [ 5 ] and 3D environment close to the extracellular matrix of native tissues, high biocompatibility, low immunogenicity in vivo and controlled biodegradability [ 6 , 7 , 8 ], alginate hydrogels have been widely used in medicine and medicine-related research [ 3 ]. This includes delivery vehicles in cancer treatment [ 9 ], wound dressing [ 4 ], mammalian cell culture in biomedical studies, tissue regeneration with protein and cell delivery, engineering of various tissues/organs [ 10 , 11 , 12 ] including bladder regeneration [ 13 ], bone tissue engineering [ 14 ], and a protective carrier for cryopreservation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the preservation of the structural elements of the hydrogel should contribute to the preservation of the cellular component of the scaffold. Several studies have demonstrated that the use of hydrogel capsules for the cryopreservation of cells makes it possible to minimize the damaging effects associated with cryostorage [ 41 , 42 , 43 ]. Hydrogel scaffolds generally have a three-dimensional structure and have biomimetic properties comparable to natural tissues [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of other substrates that allow cell adhesion such as collagen to hydrogel matrix may solve this problem and promote cell proliferation [36,37]. The present system with high biocompatibility and biodegradability might provide efficient cell storage media that does not require freezing as well—if the observed sedimentation of the cells can be prevented, for example, by adjusting the specific gravity of G-quadruplex hydrogels [38,39,40].…”
Section: Discussionmentioning
confidence: 99%